Perancangan dan Implementasi Aplikasi Sistem Informasi Manajemen Ruangan Berbasis Web (Studi Kasus: Bina Darma Salatiga) - Ramana Agung Saputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The purpose of this research is to assist the transaction process that occurs at the Bina Darma Foundation, especially for the rental of multi-purpose rooms, study rooms and bedrooms. In managing the use of existing facilities, the operational staff still uses the traditional method, meaning that the customer must visit the operational office to place an order by including some information in the book. This is the main reason for researchers to create a web-based application using a PHP framework where everyone can place an order only by visiting the Bina Darma website address, selecting the required facilities, and making payments. It can be concluded that the related parties, both ordering and operational staff, are easy and efficient in the ordering process as well as in managing administrative data.